P167 IgG4 related disease: response to immunosuppressive therapy: a single centre retrospective study in the United Kingdom. (26th April 2021) - Sangle, Shirish; Morton, Neil T; Casian, Alina; Nel, Louise; Hanna, Jennifer; Fernando, Archana; Bell, Rachel; Taylor, Peter; Pattison, James; O'Brien, Tim; D'Cruz, David
Abstract: Background/Aims IgG4 related disease (IgG4-RD) is a rare immune-mediated condition, increasingly being recognised as a multi-organ disorder. It is a relatively new entity and the precise prevalence is not known. It is a chronic fibro-inflammatory condition with raised circulating levels of immunoglobulin G4 and accumulation of plasma cells and fibrosis in the affected tissue. We report a retrospective observational study of patients with IgG4 related disease (IgG4-RD). Methods We conducted a retrospective observational study of patients seen at Guy's and St Thomas' NHS Foundation Trust Hospitals, London, UK. The data collected was analysed for clinical presentation, laboratory markers of inflammation, immunoglobulin subsets, autoantibody profiles, imaging and histopathology and compared to the 2019 ACR/EULAR criteria to determine a confirmed diagnosis of IgG4-RD. Data was also collected post standard-of-care treatment, including patient clinical outcomes and possible improvement. Results The study included a multi-ethnic cohort of 83 patients with multi-organ involvement. Fifty-nine of the eighty-three patients were classified as confirmed IgG4-RD (71%). Seventy one patients had biopsies of which 49 of the 59 (91%) confirmed IgG4-RD patients had biopsies consistent with IgG4-RD. Fifty patients underwent PET-CT scanning of which uptake was seen in 76% of those with confirmed IgG4-RD (26/34). Immunoglobulin IgG subclass analysis showed significantly higher IgG4 levels in the confirmed IgG4-RD group as compared to possible IgG4. Treatments were with corticosteroids and immunosuppressants such as azathioprine, methotrexate, mycophenolate, cyclophosphamide and rituximab. Conclusion IgG4-RD is a fibro-inflammatory disorder involving multiple organs. If not treated adequately may develop severe organ damage. It often responds to corticosteroids but may require other immunosuppressive therapy. Treatment with biologics such as B cell depletion therapy results are encouraging. Disclosure S. Sangle: None. N.T. Morton: None. A. Casian: None. L. Nel: None. J. Hanna: None. A. Fernando: None. R. Bell: None. P. Taylor: None. J. Pattison: None. T. O'Brien: None. D. D'Cruz: None.